Role of geo-potential models in gravity field determination - Manandhar, Niraj; Forsberg, Rene (Journal on Geoinformatics, Nepal, 2009)
This paper sets out to describe the developments of geopotential models and its role in gravity field determination. The paper also focuses in different geopotential models those are available and in use from 1980 onwards till at present with major emphasis placed on WGS84 EGM96 geopotential model.